Strategic Human Resource Management and Employee Engagement in Australia - Anderson, Mason (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the strategic human resource management and employee engagement in Australia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: In Australia, Strategic Human Resource Management (SHRM) practices have shown significant impact on employee engagement across various sectors. Studies consistently highlight that organizations implementing effective SHRM strategies, such as performance management systems and supportive leadership styles, experience higher levels of engagement among employees. Leadership, especially through transformational styles, plays a crucial role in inspiring teams and fostering a positive work environment. Aligning SHRM practices with a supportive organizational culture further enhances their effectiveness in promoting employee commitment and productivity. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, social exchange theory (SET) & high-involvement management (HIM) theory may be used to anchor future studies on strategic human resource management and employee engagement in Australia. Organizations should tailor their SHRM strategies to align with their unique organizational goals, culture, and employee demographics. Governments can support SHRM and employee engagement initiatives through regulatory frameworks that encourage investment in employee development, fair labor practices, and work-life balance.